SPECIFIC CHARACTERISTICS OF ORGANIZING AN INVESTMENT PROPERTY ACCOUNT (British Journal of Global Ecology and Sustainable Development, 2024)
The article reveals aspects of accounting of investment property in joint-stock companies based on international standards "Investment real estate" No. 40 IAS, reflection in accounting transfers and reflection in relevant items of financial statements.